Beyond faith and foxholes: vernacular religion and asymmetrical warfare within contemporary IDF combat units. (17th February 2020) - Stern, Nehemia; Ben Shalom, Uzi
ABSTRACT: This paper explores the vernacular roles that religious practices and experiences play within contemporary combat units of the Israel Defense Forces (IDF). We argue for an anthropological perspective that highlights the modes through which rituals serve efficacious – as opposed to semiotic – ends. In this way, we seek to push back against what we term the 'faith in a foxhole' paradigm, where religion is primarily seen as a meaning-making system whose nearly sole function is to aid soldiers in coping with the chaos and uncertainty of combat. We demonstrate how amidst the low-level and long-term style of contemporary asymmetrical warfare, ritual practices can often function less as the matrix for broader meaning making systems but are rather mobilized in ways that are meant to support certain practical and pragmatic goals. The article concludes that while scholars have mostly focused attention on the institutional forces and political consequences of 'religionization' within Israeli society, they have missed the many vernacular ways in which Israelis mobilize and instrumentalize their use of ritual and religious practices in both military and civilian contexts.